Hepatectomy extended by hepatocarcinoma in non cirrhotic patient - Cornejo-Carrasco, Consuelo Elsa (2018)
Hepatocarcinoma is the second cause of death in the world related to cancer and in our country we find patients with large liver tumors that are unresectable and are only tributaries of palliative treatments with little survival, however with an adequate selection of patients in teams multidisciplinary we can offer an extended hepatectomy to many of these patients, so we present the case of a young adult patient with hepatitis B and giant hepatocarcinoma to which we performed an extended left hepatectomy is disease free survival at 14 months after surgery.   DOI 10.25176/RFMH.v18.n4.1738